Effect of copper-nickel interlayer thickness on laser welding-brazing of Mg/Ti alloy. (July 2019) - Auwal, S.T.; Ramesh, S.; Zhang, Zequn; Yusof, F.; Liu, Jinge; Tan, Caiwang; Manladan, S.M.; Tarlochan, F.
Highlights: Join Mg alloy to titanium with varied thickness Cu-Ni coating using laser welding-brazing process. Different interlayer elements content were found to exert varied strengthening influence. The optimum fracture load was obtained with appropriate thickness of Cu-Ni coating. Abstract: Dissimilar lap joining of AZ31B Mg alloy to Cu-Ni coated Ti-6Al-4V was carried out by laser welding-brazing method. The effect of Cu and Ni contents on interfacial reaction and joint fracture load were analyzed. For the joint in which the Ni coating (15.36 µm) was thicker than the Cu coating (5.47 µm), thick intermetallic compound (IMC) composed of a mixture of light gray Al-Ni-Ti + Ti3 Al + Ti2 Ni phases mingled with dark gray Ti3 Al was produced at the interface. In comparison, a mixed interfacial reaction layer consisted of Ti2 Ni and Ti3 Al was formed from the direct irradiation zone to the weld toe zone of the joint with comparable Ni and Cu coating thicknesses (10.78 µm Cu–9.30 µm Ni). In this case, the thickness of the mixed layer was below the critical thickness of 10 µm. For the joint in which the Cu coating is much higher than the Ni coating thickness (17.12 µm Cu–4.23 µm Ni), Ti3 Al and Ti2 Ni mixed reaction layer was produced at the brazed interface of direct irradiation zone, whereas, only Ti3 Al phase was formed at the middle zone. At the weld toe zone, Ti2 Cu uneven interfacial reaction layer was evolved. With increasing Cu and decreasing Ni coating thicknesses, the fracture load first increased and then slightly decreased, the maximum tensile-shear fracture load attained 2020 N for joints with comparable Cu and Ni coating thicknesses. This is twofold higher than that of uncoated joint. The tensile-shear investigation showed that the joint would fracture at the fusion zone when the coating thickness of Ni was comparable or higher than Cu. In contrast, interfacial failure was observed when the thickness of Cu was much higher than the Ni. For the joint with interfacial failure mode, tear ridge was observed from the fracture surface, whereas, the fusion zone fracture surfaces was noted to display a typical dimple feature.